POLICY RESPONSES DURING THE TRUMP ADMINISTRATION TO OLDER PEOPLE'S GROWING ECONOMIC RISK EXPOSURE. (11th November 2018) - Weller, C; Tolson, M E
Abstract: Economic risk exposure especially through increased labor market volatility and growing caregiving responsibilities has risen for older Americans. At the same time, key protections such as unemployment insurance and Social Security have declined, while other protections, particularly in the private market are limited or non-existent. In virtually all instances, the Trump administration has already moved to weaken existing protections. And, it has offered either no proposals or very limited proposals to increase protections in the private sector, for instance, by offering households tax deductions for caregiving costs. This approach would largely benefit higher-income households and offer few or no benefits to low-income and middle-income households. As a result, an aging population will increasingly face rising economic risks on their own.